A 4D automatic simulation tool for construction resource planning: a case study. Issue 5 (21st September 2015) - Professor Monty Sutrisna and Professor Mohan M. Kumaraswamy, Associate; Li, Heng; Chan, Greg; Skitmore, Martin; Huang, Ting
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Traditional construction planning relies upon the critical path method and bar charts. Both of these methods suffer from visualization and timing issues that could be addressed by 4D technology specifically geared to meet the needs of the construction industry. The purpose of this paper is to propose a new construction planning approach based on simulation by using a game engine. Design/methodology/approach – A 4D automatic simulation tool was developed and a case study was carried out. The proposed tool was used to simulate and optimize the plans for the installation of a temporary platform for piling in a civil construction project in Hong Kong. The tool simulated the result of the construction process with three variables: equipment, site layout and schedule. Through this, the construction team was able to repeatedly simulate a range of options. Findings – The results indicate that the proposed approach can provide a user-friendly 4D simulation platform for the construction industry. The simulation can also identify the solution being sought by the construction team. The paper also identifies directions for further development of the 4D technology as an aid in construction planning and decision making. Research limitations/implications – The tests on the tool are limited to a single case study and further research is needed to test the use of game engines for construction planning in different construction projects to verify its effectiveness. Future research could also explore the use of alternative game engines and compare their performance and results. Originality/value – The authors proposed the use of game engine to simulate the construction process based on resources, working space and construction schedule. The developed tool can be used by end-users without simulation experience.